2022
DOI: 10.3390/molecules27154931
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Antiplasmodial and Cytotoxic Activities of Green Synthesized Iron Oxide Nanoparticles Using Nephrolepis exaltata Aqueous Extract

Abstract: The use of non-toxic synthesis of iron oxide nanoparticles (FeO NPs) by an aqueous plant extract has proven to be a viable and environmentally friendly method. Therefore, the present investigation is based on the FeO NPs synthesis by means of FeCl3·6H2O as a precursor, and the plant extract of Nephrolepis exaltata (N. exaltata) serves as a capping and reducing agent. Various techniques were used to examine the synthesized FeO NPs, such as UV-Visible Spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The IRs of H@Ag-NPs were located at nine peaks of 3424.7 [ 66 ], 2928.8 [ 67 ], 2861.8 [ 68 ], 1634.0 [ 69 ], 1510.3, 1386.5, 1240.2, 1059.7 [ 70 ], and 587.6 cm −1 , corresponding to strong, broad O-H stretching of alcohol; medium C-H stretching of alkane; medium C-H stretching of alkane; medium C=C stretching of alkene; strong N-O stretching of nitrocompound; medium C-H stretching of aldehyde; medium C-N stretching of amine; strong C-O stretching of primary alcohol; and strong C-Cl stretching of halocompound. FTIR peaks of H@Au-NPs occurred at 3424.7, 2928.8, 2861.8, 1747.4 [ 68 ], 1634.0, 1465.9 [ 68 ], 1231.0 [ 70 ], 1173.2 [ 71 ], 1059.7 [ 70 ], and 582.0 cm −1 , corresponding to strong, broad O-H stretching of alcohol; medium C-H stretching of alkane; medium C-H stretching of alkane; strong C=O stretching of esters or δ-lactone; strong C=C stretching of alkene; medium C-H bending of alkane; medium C-N stretching of amine; strong C-O stretching of tertiary alcohol or ester; strong C-O stretching of primary alcohol; and strong C-Cl stretching of halocompound. By analyzing the IR spectra of both plant extract and NPs, it was found that the main functional groups on the NPs’ surface were O-H or C-O of alcohol, N-O of nitrocompound, C-N of amine and C-H of hydrocarbons (essential oils/terpenes), suggesting that these biomolecules might mitigate the synthesis process of NPs as reducing and capping agents [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The IRs of H@Ag-NPs were located at nine peaks of 3424.7 [ 66 ], 2928.8 [ 67 ], 2861.8 [ 68 ], 1634.0 [ 69 ], 1510.3, 1386.5, 1240.2, 1059.7 [ 70 ], and 587.6 cm −1 , corresponding to strong, broad O-H stretching of alcohol; medium C-H stretching of alkane; medium C-H stretching of alkane; medium C=C stretching of alkene; strong N-O stretching of nitrocompound; medium C-H stretching of aldehyde; medium C-N stretching of amine; strong C-O stretching of primary alcohol; and strong C-Cl stretching of halocompound. FTIR peaks of H@Au-NPs occurred at 3424.7, 2928.8, 2861.8, 1747.4 [ 68 ], 1634.0, 1465.9 [ 68 ], 1231.0 [ 70 ], 1173.2 [ 71 ], 1059.7 [ 70 ], and 582.0 cm −1 , corresponding to strong, broad O-H stretching of alcohol; medium C-H stretching of alkane; medium C-H stretching of alkane; strong C=O stretching of esters or δ-lactone; strong C=C stretching of alkene; medium C-H bending of alkane; medium C-N stretching of amine; strong C-O stretching of tertiary alcohol or ester; strong C-O stretching of primary alcohol; and strong C-Cl stretching of halocompound. By analyzing the IR spectra of both plant extract and NPs, it was found that the main functional groups on the NPs’ surface were O-H or C-O of alcohol, N-O of nitrocompound, C-N of amine and C-H of hydrocarbons (essential oils/terpenes), suggesting that these biomolecules might mitigate the synthesis process of NPs as reducing and capping agents [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed the capability of silver nanoparticles biosynthesized using plant extracts of Salvia spinosa grown In vitro [ 42 ]. Faisal et al [ 43 ] reported on the toxicity of the biosynthesized nanoparticles on human PMBCs in in vitro experiments. The absence of toxicity in nanoparticles provides more stability for subsequent pharmaceutical and other medical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular mechanisms involve the enzymatic reduction of metal oxide ions through the electrostatic binding of metal ions to -COOH groups of the microbial cell wall, metal ions diffuse into the cell and interact with enzymes to form metal oxide nanoparticles [30,31]. For this type of synthesis, the microorganisms are grown under optimal conditions, then the biomass is washed with sterile water and incubated with a solution of metal salts until a color change indicates the nanoparticle synthesis [26] (Figure 1).…”
Section: Synthesis Of Iron Oxide Nanoparticles Using Microorganismsmentioning
confidence: 99%